A blend of selected botanicals maintains intestinal epithelial integrity and reduces susceptibility to Escherichia coli F4 infection by modulating acute and chronic inflammation in vitro - Bonetti, Andrea; Toschi, Andrea; Tugnoli, Benedetta; Piva, Andrea; Grilli, Ester (Frontiers in Veterinary Science, 2023)
In the pig production cycle, the most delicate phase is weaning, a sudden and early change that requires a fast adaptation, at the cost of developing inflammation and oxidation, especially at the intestinal level. In this period, pathogens like enterotoxigenic Escherichia coli (ETEC) contribute to the establishment of diarrhea, with long-lasting detrimental effects. Botanicals and their single bioactive components represent sustainable well-recognized tools in animal nutrition thanks to their wide-ranging beneficial functions. The aim of this study was to investigate the in vitro mechanism of action of a blend of botanicals (BOT), composed by thymol, grapeseed extract, and capsicum oleoresin, in supporting intestinal cell health during inflammatory challenges and ETEC infections. To reach this, we performed inflammatory and ETEC challenges on Caco-2 cells treated with BOT, measuring epithelial integrity, cellular oxidative stress, bacterial translocation and adhesion, gene expression levels, and examining tight junction distribution. BOT protected enterocytes against acute inflammation: while the challenge reduced epithelial tightness by 40%, BOT significantly limited its drop to 30%, also allowing faster recovery rates. In the case of chronic inflammation, BOT systematically improved by an average 25% the integrity of challenged cells (p < 0.05).. Moreover, when cells were infected with ETEC, BOT maintained epithelial integrity at the same level of an effective antibiotic, and significantly reduced bacterial translocation by 1 log average. The mode of action of BOT was strictly related to the modulation of the inflammatory response, protecting tight junctions’ expression and structure. In addition, BOT influenced ETEC adhesion to intestinal cells (-4%, p < 0.05), also thanks to the reduction of enterocytes’ susceptibility to pathogens. Finally, BOT effectively scavenged reactive oxygen species generated by inflammatory and H2O2 challenges, thus alleviating oxidative stress by 40% compared to challenge (p < 0.05). These results support the employment of BOT in piglets at weaning to help managing bacterial infections and relieving transient or prolonged stressful states thanks to the modulation of host-pathogen interaction and the fine-tuning activity on the inflammatory tone.